Ortodoksi dan Heterodoksi Tafsir - Dadang Darmawan (Refleksi, 2012)
This article tries to explain that the rejection of ‘ulamās towards Qur’ānic exegesis books (tafsīrs) is a reflection of orthodoxies protest against what they perceived as heterodoxies tafsīrs. This article also supports Arkoun’s idea that the orthodox exegesis is subject to change. This is against the idea of several Islamic scholars who perceived orthodox exegesis as something fixed and static. They believed that Sunnī is a criterion as to decide whether the exegesis belongs to the orthodox or heterodox. This article reveales that despite the long standing of Sunnīs exegesis, it is proved not to be permanent.DOI: 10.15408/ref.v13i2.898